NORTHERN ENGLAND SERPUKHOVIAN (EARLY NAMURIAN) FARFIELD BRACHIOPOD AND PLANT ISOTOPE RESPONSES TO SOUTHERN HEMISPHERE GLACIATION - M. H. Stephenson; P. Cózar; J. Melanie; D. Millward; L. Angiolini; F. Jadoul (2010)
The Serpukhovian was a period of climatic change in Gondwana with glaciation being initiated in limited areas of eastern Australia, South America and Tibet. The Serpukhovian is poorly represented by farfield isotope studies. Previous surveys of isotope data from brachiopod carbonate have few Serpukhovian sample points, as well as low values questioned by previous workers. Similarly organic δ 13 C which mainly tracks terrestrial plant tissue is poorly represented in the Serpukhovian. The Woodland, Throckley and Rowlands Gill boreholes (northern England) contain a Serpukhovian to Bashkirian farfield record newly dated by foraminiferans. δ 18 O values from late Serpukhovian Woodland brachiopods vary between -3.4 and -6.3‰, and δ 13 C varies between -2.0 and + 3.2‰, confirming low values recorded elsewhere and suggesting a δ 18 O seawater (w) value of around -1.8‰ VSMOW, and therefore an absence of widespread ice-caps. The organic carbon δ 13 C increasing trend in the Throckley Borehole (Serpukhovian to Bashkirian; c. -24 to c. -22‰), and the Rowlands Gill Borehole (Serpukhovian; c. -24 to c. -23‰) indicates large-scale burial of organic material, probably in burgeoning lycophyte-dominated coal forest and would imply a steady fall in pCO 2 . Therefore these high resolution data show that at least one substantial period of the Serpukhovian cannot have been glaciated. The steady fall in Serpukhovian pCO 2 appears not to have caused large-scale glaciation until the early Bashkirian, but a scenario of coalescing upland icecaps through the Serpukhovian with a background of decreasing pCO 2 , appears to be similar to the process that initiated Cenozoic Antarctic glaciation.